2020
DOI: 10.1590/1678-4324-2020180571
|View full text |Cite
|
Sign up to set email alerts
|

Possible Metsulfuron Herbicide Detoxification by a Oryza sativa L. Glutathione S-transferase Enzyme.

Abstract: Rice (Oryza sativa L.) is one of the most important crops in the world, and it is considered the primary source of nutritional layout in developing countries in Asia. The glutathione S-transferases (GSTs) superfamily confers to rice protection against biotic and abiotic stress, and herbicide resistance. However, the three-dimensional structure of a GST Tau class, is unsolved. The objectives of this work were to develop a reliable comparative model for the s-transferase glutathione class Tau 4 from rice, and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Another large portion of the studied proteins responsible for glutathione metabolism was observed and the amounts of these proteins were higher in the herbicide-treated sample and in F. culmorum -inoculated wheat. Plant glutathione transferase (theoretical MW 24,984 Da, in gel ~24 kDa), an enzyme capable of catalyzing the conjugation and detoxification of herbicides, was found in higher amounts in all 2,4-D-treated cultures in this study [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another large portion of the studied proteins responsible for glutathione metabolism was observed and the amounts of these proteins were higher in the herbicide-treated sample and in F. culmorum -inoculated wheat. Plant glutathione transferase (theoretical MW 24,984 Da, in gel ~24 kDa), an enzyme capable of catalyzing the conjugation and detoxification of herbicides, was found in higher amounts in all 2,4-D-treated cultures in this study [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The alignment revealed that the H-site of GSTU7 contains a Met–Trp–Ala motif that is also present in OsGSTU4 from rice. The overexpression of OsGSTU4 in Arabidopsis has proven to generate more tolerant plants toward salt stress and MV-induced photooxidative stress, while in silico characterization led to the hypothesis that OsGSTU4 might detoxify the herbicide metsulfuron ( Sharma et al, 2014 ; Amador et al, 2020 ). These results together suggest a conserved function of distinct TAU GSTs and may provide leads for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The detoxification mechanisms of xenobiotics are known to be a multi‐step process involving several proteins in each phase. The current knowledge of the toxicity response of xenobiotics can be divided into contaminant transformation (phase I), conjugation (phase II), and excretion (phase III), which are well‐conserved detoxification mechanisms in a wide range of organisms 23–26 . Initially, cytochrome P450 (CYP) transforms the xenobiotics into a more soluble compound, then glutathione S‐transferase (GST) conjugates the xenobiotics with glutathione (GSHs) and transports the contaminants into ATP‐binding cassette (ABC) transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I reactions convert herbicide into less active compounds by the cytochrome P450s enzymes (CYPs) 22,23 . Phase II reactions conjugate herbicide to other water‐soluble substances by glutathione S‐transferases (GSTs) 24 . Phase III reactions involve transporting conjugated glyphosate into the vacuole or out of the cell by ATP‐binding cassette (ABC) transporters 25,26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation